Elastin fibers display a versatile microfibril network in articular cartilage depending on the mechanical microenvironments - He, Bo; Wu, Jianping; Chen, Honghui; Kirk, Thomas; Xu, Jiake (Elsevier Science, 2013)
Elastin fibers are major extracellular matrix macromolecules that are critical in maintaining the elasticity and resilience of tissues such as blood vessels, lungs and skins. However, the role of elastin in articular cartilage is poorly defined. The present study investigated the organization of elastin fiber in articular cartilage, its relationship to collagen fibers and the architecture of elastin fibers from different mechanical environments by using a kangaroo model. Five morphologies of elastin fibers were identified: Straight fiber, straight fiber with branches, branching fibers directly associated with chondrocyte, wave fiber and fine elastin. The architecture of the elastin network varied significantly with cartilage depth. In the most superficial layer of tibial plateau articular cartilage, dense elastin fibers formed a distinctive cobweb-like meshwork which was parallel to the cartilage surface. In the superficial zone, elastin fibers were well organized in a preferred orientation which was parallel to collagen fibers. In the deep zone, no detectable elastin fiber was found. Moreover, differences in the organization of elastin fibers were also observed between articular cartilage from the tibial plateau, femoral condyle, and distal humerus. This study unravels the detailed microarchitecture of elastin fibers which display a well-organized three-dimensional versatile network in articular cartilage. Our findings imply that elastin fibers may play a crucial role in maintaining the integrity, elasticity, and the mechanical properties of articular cartilage, and that the local mechanical environment affects the architectural development of elastin fibers.